PENERAPAN PRINSIP 5R (REDUCE, REUSE, RECYCLE, REPLANT DAN REPLACE) SEBAGAI UPAYA EFEKTIF MENANGANI MASALAH SAMPAH RUMAHTANGGA - Nyayu Neti Arianti; Ellys Yuliarti; Marlin - (DHARMA RAFLESIA, 2018)
The aims of this activity are 1) to introduce and to apply the 5R principles to handle the household waste, 2)  to introduce and to apply composting method of  the organic household waste in Takakura Bin, 3) to introduce and to apply the producing method of recycled paper, and 4) to evaluate the technology which introduced and applied. The participants are 11 housewives. The activity methods are extention and practicing (learning by doing). All of participants are exited.  The results of evaluation analysis show that 78,41 % said that the technology which introduced and applied are very good and 21,59 % participants said that the technology are good. Keywords: household waste, 5R principles, takakura bin, recycled paper